2021
DOI: 10.1021/acs.inorgchem.1c00852
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Deep-Red Light-Emitting Electrochemical Cell Based on a Trinuclear Ruthenium(II)–Silver(I) Complex

Abstract: Turn-on time is a key factor for lighting devices to be of practical application. To decrease the turn-on time value of a deep-red light-emitting electrochemical cells (DR-LECs), two novel approaches based on molecularly engineered ruthenium phenanthroimidazole complexes were introduced. First, we found that with the incorporation of ionic methylpyridinium group to phenanthroimidazole ligand, the turn-on time of the DR-LECs device was dramatically reduced, from 79 to 27 s. By complexation of ruthenium emitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 69 publications
(96 reference statements)
0
21
0
Order By: Relevance
“…[52] In the same year, Pashaei et al reported Ru II À Ag I À Ru II complexes based on the phenanthroimidazole ligand containing a pyridine moiety. [50] Silver ion was selected as a dimerizing agent owing to the significant photophysical properties of its complexes in the solid state. The outstanding EL characteristics of complex 38 (Figure 3) are likely due to the increase in the concentrations of mobile counterions, leading to an increase in the ionic property of the emissive layer, rendering shorter turn-on time.…”
Section: Multinuclear Ruthenium Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[52] In the same year, Pashaei et al reported Ru II À Ag I À Ru II complexes based on the phenanthroimidazole ligand containing a pyridine moiety. [50] Silver ion was selected as a dimerizing agent owing to the significant photophysical properties of its complexes in the solid state. The outstanding EL characteristics of complex 38 (Figure 3) are likely due to the increase in the concentrations of mobile counterions, leading to an increase in the ionic property of the emissive layer, rendering shorter turn-on time.…”
Section: Multinuclear Ruthenium Complexesmentioning
confidence: 99%
“…To decrease the turn‐on time of deep red LECs, the ionic methylpyridinium group was attached to the phenanthroimidazole ligand of a ruthenium complex (complex 27 , Figure 2) to form the complex 28 (Figure 2) by Bideh et al. in 2021 [50] . With the ionic moiety, the LECs based on complex 28 showed dramatically reduced turn‐on time from 79 to 27 s. All reported device data of the LECs based on mononuclear ruthenium complexes ( 1 – 28 ) are summarized in Table 1.…”
Section: Materials For Long‐wavelength Lecsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unique photophysical properties of iTMCs, such as the high external quantum efficiency (EQE) and long half-time, especially Ir­(III) organometallic complexes, , Cu­(I) complexes, , and Ru­(II) polypyridine complexes, have led to the design of new derivatives. Nevertheless, various iTMCs such as Pd­(II), Zn­(II), Pt­(II), Ir­(III)–Au­(I), and Ru­(II)–Ag­(I) have also been used in LECs as an emitter. ,,,, In film-processing, iTMCs are very useful because a single component is used in the film, and it acts as a charge transport and emissive material. The first iTMC-based LEC, fabricated in 1996 by Lee et al, showed that Ru­(II) polypyridine complexes exhibit favorable electroluminescence (EL) and thermal stability properties .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, various iTMCs such as Pd(II), Zn(II), Pt(II), Ir(III)−Au(I), and Ru(II)−Ag(I) have also been used in LECs as an emitter. 18,20,23,27,28 In film-processing, iTMCs are very useful because a single component is used in the film, and it acts as a charge transport and emissive material. The first iTMC-based LEC, fabricated in 1996 by Lee et al, showed that Ru(II) polypyridine complexes exhibit favorable electroluminescence (EL) and thermal stability properties.…”
Section: Introductionmentioning
confidence: 99%